Principles of spread-spectrum communication systems - Torrieri, Don J. (Springer, 2011)
Principles of Spread-Spectrum Communication Systems, Second Edition provides a concise but lucid explanation of the fundamentals of spread-spectrum systems with an emphasis on theoretical principles. The choice of specific topics is tempered by the authors judgment of their practical significance and interest to both researchers and system designers. Throughout the book, learning is facilitated by many new or streamlined derivations of the classical theory. Problems at the end of each chapter are intended to assist readers in consolidating their knowledge and to provide practice in analytical techniques. The evolution of spread spectrum communication systems and the prominence of new mathematical methods in their design provided the motivation to undertake this new edition of the book. This edition is intended to enable readers to understand the current state-of-the-art in this field. More than 20 percent of the material in this edition is new, including a chapter on systems with iterative channel estimation, and the remainder of the material has been thoroughly revised.